EFEKTIVITS PENGELOLAAN DANA DESA DALAM PENGEMBANGAN EKONOMI DI DESA SETALIK KECAMATAN SEJANGKUNG PERSPEKTIF EKONOMI ISLAM - Aan Sumantri; Wulan Purnamasari; Arnadi (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2022)
This research departs from the phenomenon Dana Desa (DD), which is given so large, then it must be managed as well as possible. Where in the implementation of rural development programs with village funds also must involve the community, so that people feel kamajuan village-managed funds of the village. For the creation of self-sufficient village then the increase of the economic potential of the village-based society should be raised. In the improvement of the economy of the village then required the involvement of the community around especially in especially in the rural development and empowerment of village communities. Empowerment as a process of developing, self-reliance,and menswadayakan. The purpose of this study is to understand the management of the village fund and to analyze the effectiveness of the use of village funds in the development of the economy. This study is prepared based on the field research (field research) by using a qualitative approach. While the technique of data collection using observation and interview, and dig through the primary data source and secondary data sources. Then once the data is collected, then analyzed by using the method of inductive and descriptive analytical. The results of this research budget comes from the state BUDGET, which named Dana Desa (DD) should be maximized in order to the construction of the village to be better. Effective development is development that meets the expectations of beneficiaries of rural development, more so in the economic development of the Village. With it results in the formulation of the problem is (1) the Management of the use of Village Funds is the activity that is designed to village development and community empowerment. With the hope of getting welfare and the evenness of the development of the village. (2) Analysis of the effectiveness of the use of village funds in the Development of the Economy is a success against the empowerment of the community in the development of the economy, so that people can feel the success of the planning of the management of the village fund the development of the economy of the village; the economic Development or community empowerment.